2016
DOI: 10.1103/physreva.94.032123
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing quantum and classical clocks made of quantum particles

Abstract: We demonstrate that the quantum corrections to the classical arrival time for a quantum object in a potential free region of space, as computed in Phys. Rev. A 80, 030102(R) (2009), can be eliminated up to a given order of by choosing an appropriate position-dependent phase for the object's wave-function This then implies that we can make the quantum arrival time of the object as close as possible to its corresponding classical arrival time, allowing us to synchronize a classical and quantum clock which tells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This implies that the particle may be either delayed or advanced depending on the initial wavepacket ϕ(q). The effect of these quantum correction terms may be minimized up to an arbitrary order of by imprinting an appropriate position-dependent phase on the initial wavefunction [19,20].…”
Section: Expectation Value Of the Relativistic Free Time Of Arrival O...mentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the particle may be either delayed or advanced depending on the initial wavepacket ϕ(q). The effect of these quantum correction terms may be minimized up to an arbitrary order of by imprinting an appropriate position-dependent phase on the initial wavefunction [19,20].…”
Section: Expectation Value Of the Relativistic Free Time Of Arrival O...mentioning
confidence: 99%
“…One of us has shown that Pauli has made some implicit assumptions and that these were inconsistent [8]. This opens up an avenue to still consider TOA as an observable in standard quantum mechanics [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Moreover, it was discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%